Assessing the Quality of Care of Prosthodontics Services Using Rapid Assessment Procedures - Tri Budi W. Rahardjo; Roselani W. Odang (Faculty of Dentistry, Universitas Indonesia, 2015)
Quality of care (QOC) in health services is a crucial issue in the last decade, since there is a competition in relation to the era of globalization. Accordingly, the demand of quality of care in prosthodontic services has also to be considered and assessed. In this regard, Rapid Assessment procedures can be carried out to evaluate the quality of care in prosthodontic services, using many questionnaire - based, secondary data analysis, interview and direct observation. This assessment will be concerned on the pronciples, concept and practices in prosthodontic, which will be associated with the satisfaction of both clients and providers. Since then, the standard quality of care will be obtained as a tool to evaluate of prosthodontic services. We hope that we will be able to provide better services in the future.